Solid waste composite stable material for road and construction process thereof

By combining solid waste composites and modified lignin fibers in stable materials for road construction, the material ratio and construction process are optimized, and the problem of material strength optimization ignores dispersion ability and stability in the prior art is solved, and higher mechanical properties and crack resistance are achieved.

CN119797878AInactive Publication Date: 2025-04-11HEBEI PROVINCIAL COMM PLANNING & DESIGN INST
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510286622.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-12
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing stable materials for road construction ignore the dispersion ability and stability of the raw materials when the strength is optimized, resulting in uneven mixing of materials, segregation, and mechanical properties, and large drying and shrinking are prone to reflective cracks.

Method used

Solid waste composite stabilized materials are used to combine graded gravel and solid waste composites, and add modified lignin fibers, polycarboxylic acid water reducing agents and modifiers to optimize the material's ratio and construction process to improve the mechanical properties and stability of the material.

Benefits of technology

It improves the mechanical properties, stability and anti-reflective crack performance of solid waste composite stable materials, effectively recycles and utilizes scrap steel slag, slag and other materials, and reduces the self-shrinkage rate and crack generation of materials.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of road engineering, and particularly discloses a solid waste composite stable material for a road and a construction process thereof. The solid waste composite stable material comprises the following raw materials in parts by mass: 400-450 parts of graded broken stone, 20-25 parts of water, 25-30 parts of modified lignin fibers and 70-80 parts of a solid waste composite material, the solid waste composite material comprises slag powder, composite alkaline residue powder, fly ash, steel slag powder and desulfurized gypsum in a mass ratio of (4-5): (2-3): 1: 1: (2-3); the preparation method of the modified lignin fiber comprises the following steps: modifying citric acid with bromoethane, and then adding guar gum hydroxypropyl trimethyl ammonium chloride and zinc sulfate to prepare a modifier; the preparation method comprises the following steps: modifying lignin fibers with (3-bromopropyl) trimethoxysilane to obtain lignin fibers A; taking a polycarboxylate superplasticizer, the lignin fiber A, a modifier and tetrahydrofuran, uniformly stirring, reacting, and removing the solvent to obtain the modified lignin fiber.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road engineering, and specifically discloses a solid waste composite stabilizing material for roads and a construction process thereof. Background Art

[0002] The strength of road construction materials has a great impact on the service life of roads. In the prior art, the strength of stabilizing materials is improved by optimizing the raw materials and proportions of the stabilizing materials, but the dispersion ability and stability of each raw material in the stabilizing materials are ignored, resulting in problems such as uneven material mixing, segregation, and decreased mechanical properties. In addition, some road construction materials have large drying shrinkage and are prone to shrinkage cracking, which causes reflective cracks in the pavement structure; therefore, it is of great significance to study a solid waste composite stabilizing material for roads and its construction process to improve its strength and reduce shrinkage. Summary of the invention

[0003] The purpose of the present invention is to provide a solid waste composite stabilization material and a construction process thereof to solve the problems raised in the prior art.

[0004] To achieve the above-mentioned purpose, the present invention provides the following technical scheme: a solid waste composite stabilization material: comprising the following raw materials, calculated by weight: 400-450 parts of graded crushed stone, 20-25 parts of water, 25-30 parts of modified lignin fiber, and 70-80 parts of solid waste composite material; the solid waste composite material comprises slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a mass ratio of (4-5): (2-3): 1:1: (2-3).

[0005] More optimally, the synthetic gradation of the graded crushed stone is specifically as follows: the percentage of passing through a sieve hole size of 19 mm is 100%, the percentage of passing through a sieve hole size of 16 mm is 88-93%, the percentage of passing through a sieve hole size of 13.2 mm is 76-86%, the percentage of passing through a sieve hole size of 9.5 mm is 59-72%, the percentage of passing through a sieve hole size of 4.75 mm is 35-45%, the percentage of passing through a sieve hole size of 2.36 mm is 22-31%, the percentage of passing through a sieve hole size of 1.18 mm is 13-22%, the percentage of passing through a sieve hole size of 0.6 mm is 8-15%, the percentage of passing through a sieve hole size of 0.3 mm is 5-10%, the percentage of passing through a sieve hole size of 0.15 mm is 3-7%, and the percentage of passing through a sieve hole size of 0.075 mm is 2-5%.

[0006] More optimally, the graded crushed stone can be replaced by clay; the liquid limit of the clay is equal to 39, the plastic limit is equal to 23, and the plasticity index is equal to 16; The slag powder is obtained by grinding granulated blast furnace slag powder, and the specific surface area is not less than 500m 2 / kg; The composite alkali slag powder is alkali slag sand, white mud and salt mud in a mass ratio of (5-10): (65-85): (10-25). The composite alkali slag powder is obtained by centrifuging, drying, breaking up and grinding the alkali slag sand. The specific surface area is not less than 300m 2 / kg; The fly ash is secondary fly ash; The steel slag powder is obtained by grinding converter steel slag powder, and the specific surface area is not less than 400m 2 / kg; Desulfurized gypsum is desulfurized gypsum obtained from thermal power plants, with a specific surface area of ​​not less than 500m 2 / kg.

[0007] More optimally, the preparation of the modified lignin fiber includes the following steps: Step 1: Take ascorbic acid, dodecyl mercaptan, and water, stir evenly to obtain component A; take hydroxyethyl acrylate, acrylic acid, maleic anhydride, hydrogen peroxide, and water, stir evenly to obtain component B; take isopentanol polyoxyethylene ether and water, stir evenly, add component A and component B dropwise at 40-50° C., the adding time is 3-4 hours and 3-3.5 hours respectively, after the addition is completed, stir at room temperature for 2-4 hours, adjust the pH to 6-7, and obtain a polycarboxylic acid water reducer; Step 2: stir citric acid, ethyl bromide, sodium carbonate and tetrahydrofuran evenly, react at 70-80°C for 5-7h to obtain modified citric acid; add guar gum hydroxypropyltrimethylammonium chloride and zinc sulfate, stir evenly, stir at 110-120°C for 8-10h, remove the solvent, and obtain a modifier; Step 3: Take (3-bromopropyl)trimethoxysilane, add it to water and ethanol, heat to 40~50℃ and stir for 1~2h, add lignin fiber, keep warm and stir for 4~6h, filter out the solid, dry it, and obtain lignin fiber A; take polycarboxylic acid water reducer, lignin fiber A, modifier, tetrahydrofuran, stir evenly, react at 70~80℃ for 6~7h, remove the solvent, and obtain modified lignin fiber.

[0008] More optimally, the polycarboxylate water-reducing agent comprises the following raw materials, by mass: 1-2 parts of ascorbic acid, 1-2 parts of dodecyl mercaptan, 40-50 parts of hydroxyethyl acrylate, 50-60 parts of acrylic acid, 30-40 parts of maleic anhydride, 1-2 parts of hydrogen peroxide, and 250-260 parts of isopentanol polyoxyethylene ether.

[0009] More optimally, the modifier includes the following raw materials, calculated by mass: 20-25 parts of citric acid, 8-12 parts of ethyl bromide, 10-12 parts of sodium carbonate, 180-220 parts of tetrahydrofuran, 8-12 parts of guar gum hydroxypropyltrimethylammonium chloride, and 0.5-1 part of zinc sulfate.

[0010] More optimally, the lignin fiber A includes the following raw materials, calculated by mass: 1-2 parts of (3-bromopropyl)trimethoxysilane, 10-15 parts of lignin fiber; the modified lignin fiber includes the following raw materials, calculated by mass: 10-15 parts of polycarboxylic acid water reducer, 15-20 parts of lignin fiber A, and 5-8 parts of modifier.

[0011] More optimally, the lignin fiber has a length of 6-10 mm and is purchased from Kramar.

[0012] More optimally, the above-mentioned construction process of a solid waste composite stabilized material includes the following steps: taking the solid waste composite stabilized material, spreading it, and compacting it; spraying a construction additive to obtain a base layer; when the surface of the base layer is slurry-free and there is no water seepage, spreading the solid waste composite stabilized material for the second time, compacting it, and completing the construction after curing; The construction aid comprises the following raw materials, by mass percentage: 6-8% sodium coconut oil hydroxyethyl sulfonate, 8-12% formaldehyde PVA, 5-6% PVA, 5-10% carboxyl-terminated silicone oil, and the balance is water.

[0013] More optimally, the preparation of the aldehyde-modified PVA includes the following steps: preparing a 10 wt % PVA aqueous solution with PVA and water; taking 20 to 30 parts of the 10 wt % PVA aqueous solution, adjusting the pH to 3 to 4, adding 20 to 25 parts of a 1 mol / L glutaraldehyde aqueous solution, and standing at room temperature for 24 hours to obtain the aldehyde-modified PVA.

[0014] Preferably, the spraying amount of the construction additive is 0.1-0.15 kg / m 2 .

[0015] More optimally, the construction process refers to the existing technology and specifically includes the following steps: Take the solid waste composite stabilized material, spread it, and use a 20t roller for static compaction, the number of static compaction is 2 times, and the rolling speed is 25m / min; use a 32t vibratory roller for vibration compaction, after weak vibration 1 time, strong vibration 1 time, and rolling speed is 60m / min; spray construction additives to get the base layer; when the surface of the base layer is slurry-collected and there is no water seepage, spread the mixture, use a 20t roller for static compaction, the number of static compaction is 2 times, and the rolling speed is 25m / min; use a 32t vibratory roller for vibration compaction, after weak vibration 1 time, strong vibration 3 times, and rolling speed is 40m / min; use a 26t roller for static compaction, the number of static compaction is 2 times, and rolling speed is 40m / min; immediately use a one-cloth-one-film covering method for maintenance, and equip a spray sprinkler truck for watering. After 7 days of maintenance, the construction is completed.

[0016] More optimally, take the solid waste composite stabilization material, spread half of its mass, and compact it; spray the construction additive to obtain the base layer; when the surface of the base layer is slurry-saturated and there is no water seepage, spread the other half of the solid waste composite stabilization material for the second time, compact it, and complete the construction after curing.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention uses solid waste composite materials as stabilizing materials, combines them with graded crushed stones, combines the advantages of both, and improves mechanical properties, stability and anti-reflective cracking performance; the solid waste composite materials used in the present invention effectively recycle waste steel slag, slag, alkali slag, etc., and the specifications of materials such as steel slag, slag, fly ash, alkali slag, etc. used in the present invention are controlled, which is conducive to improving strength; however, the stability of steel slag, slag, and alkali slag is not easy to control, so the present invention effectively reduces cracking and other diseases caused by their poor stability by controlling the addition amount, adding modified lignin fiber, etc. Lignin fiber can prevent cracking, improve stability, and facilitate construction; the present invention combines it with a polycarboxylic acid water-reducing agent and a modifier to obtain modified lignin fiber, which is then added to improve the dispersibility of the lignin fiber; the citric acid in the modifier has a retarding effect, and can also increase the compactness of the material, reduce the self-shrinkage rate, and reduce the generation of cracks; guar gum hydroxypropyl trimethyl ammonium chloride plays the role of a thickener and a surfactant at the same time, improves construction workability, reduces surface tension, further improves the coating effect on aggregates, and improves mechanical properties; the addition amount of guar gum hydroxypropyl trimethyl ammonium chloride needs to be controlled, and excessive addition will cause the additive chain segments to be entangled, disordered, and the like, resulting in performance degradation; The solid waste composite stabilizing material prepared by the present invention uses a special construction method and sprays a construction aid. Among the construction aids, the aldehyde-modified PVA has a certain film-forming property, which can improve the flexibility and adhesion of the surface mixture on the base layer, promote the bonding strength between layers, and improve the overall strength; the aldehyde group can be cross-linked with the mixture of the upper and lower parts to achieve a coagulation-promoting effect and obtain a higher interface strength; at the same time, it can prevent the upper mixture from moving downward to cause the problem of dense upper and sparse lower parts, which is helpful to improve the overall strength. DETAILED DESCRIPTION

[0018] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0019] Unless otherwise specified, the following parts are all parts by mass and percentage by mass; Example 1: S1: Take 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water, stir evenly to obtain component A; take 40 parts of hydroxyethyl acrylate, 60 parts of acrylic acid, 30 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water, stir evenly to obtain component B; take 250 parts of isopentanol polyoxyethylene ether and 50 parts of water, stir evenly, add component A and component B dropwise at 50°C, the addition time is 4h and 3.5h respectively, after the addition is completed, stir at room temperature for 4h, adjust the pH to 7, and obtain a polycarboxylic acid water reducer; S2: 25 parts of citric acid, 12 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 12 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 2 parts of (3-bromopropyl)trimethoxysilane, add to 60 parts of water and 20 parts of ethanol, heat to 45°C and stir for 2 hours, add 15 parts of 8mm lignin fiber, keep warm and stir for 4 hours, filter out the solid, dry, and obtain lignin fiber A; take 12 parts of polycarboxylic acid water reducer, 18 parts of lignin fiber A, 6 parts of modifier, 100 parts of tetrahydrofuran, stir evenly, react at 75°C for 7 hours, remove the solvent, and obtain modified lignin fiber; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 80 parts of solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, spread half of it, compact it; spray the construction additive at a dosage of 0.12kg / m 2 , and obtain the base layer; when the surface of the base layer is slurry-free and there is no water seepage, the other half of the solid waste composite stabilized material is spread for the second time, compacted, and the construction is completed after curing to obtain the sample of Example 1; The construction aid comprises: 8% sodium coconut oil hydroxyethyl sulfonate, 12% formaldehyde PVA, 5% PVA, 8% carboxyl-terminated silicone oil, and the balance is water; Preparation steps of aldehyde-modified PVA: Take 25 parts of 10% PVA aqueous solution, adjust the pH to 4, add 25 parts of 1 mol / L glutaraldehyde aqueous solution, and let stand at room temperature for 24 hours to obtain aldehyde-modified PVA.

[0020] Example 2: S1: Take 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water, stir evenly to obtain component A; take 40 parts of hydroxyethyl acrylate, 60 parts of acrylic acid, 40 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water, stir evenly to obtain component B; take 250 parts of isopentanol polyoxyethylene ether and 50 parts of water, stir evenly, add component A and component B dropwise at 50°C, the addition time is 4h and 3.5h respectively, after the addition is completed, stir at room temperature for 4h, adjust the pH to 7, and obtain a polycarboxylic acid water reducer; S2: 20 parts of citric acid, 8 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 8 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 2 parts of (3-bromopropyl)trimethoxysilane, add to 60 parts of water and 20 parts of ethanol, heat to 45°C and stir for 2 hours, add 15 parts of 8mm lignin fiber, keep warm and stir for 4 hours, filter out the solid, dry, and obtain lignin fiber A; take 15 parts of polycarboxylic acid water reducer, 20 parts of lignin fiber A, 5 parts of modifier, 100 parts of tetrahydrofuran, stir evenly, react at 75°C for 7 hours, remove the solvent, and obtain modified lignin fiber; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 80 parts of solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, spread half of it, compact it; spray the construction additive at a dosage of 0.12kg / m 2 , and obtain the base layer; when the surface of the base layer is slurry-free and there is no water seepage, the other half of the solid waste composite stabilized material is spread for the second time, compacted, and the construction is completed after curing to obtain the sample of Example 2; The construction aid comprises: 8% sodium coconut oil hydroxyethyl sulfonate, 12% formaldehyde PVA, 5% PVA, 8% carboxyl-terminated silicone oil, and the balance is water; Preparation steps of aldehyde-modified PVA: Take 25 parts of 10% PVA aqueous solution, adjust the pH to 4, add 25 parts of 1 mol / L glutaraldehyde aqueous solution, and let stand at room temperature for 24 hours to obtain aldehyde-modified PVA.

[0021] Example 3: S1: Take 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water, stir evenly to obtain component A; take 40 parts of hydroxyethyl acrylate, 50 parts of acrylic acid, 30 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water, stir evenly to obtain component B; take 260 parts of isopentanol polyoxyethylene ether and 50 parts of water, stir evenly, add component A and component B dropwise at 50°C, the addition time is 4h and 3.5h respectively, after the addition is completed, stir at room temperature for 4h, adjust the pH to 7, and obtain a polycarboxylic acid water reducer; S2: 20 parts of citric acid, 12 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 12 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 1 part of (3-bromopropyl)trimethoxysilane, add it to 60 parts of water and 20 parts of ethanol, heat it to 45°C and stir it for 2 hours, add 10 parts of 8mm lignin fiber, keep it warm and stir it for 4 hours, filter out the solid, dry it, and obtain lignin fiber A; take 10 parts of polycarboxylic acid water reducer, 15 parts of lignin fiber A, 5 parts of modifier, 100 parts of tetrahydrofuran, stir evenly, react at 75°C for 7 hours, remove the solvent, and obtain modified lignin fiber; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 80 parts of solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, spread half of it, compact it; spray the construction additive at a dosage of 0.12kg / m 2 , and obtain the base layer; when the surface of the base layer is slurry-free and there is no water seepage, the other half of the solid waste composite stabilized material is spread for the second time, compacted, and the construction is completed after curing to obtain the sample of Example 3; The construction aid comprises: 8% sodium coconut oil hydroxyethyl sulfonate, 12% formaldehyde PVA, 5% PVA, 8% carboxyl-terminated silicone oil, and the balance is water; Preparation steps of aldehyde-modified PVA: Take 25 parts of 10% PVA aqueous solution, adjust the pH to 4, add 25 parts of 1 mol / L glutaraldehyde aqueous solution, and let stand at room temperature for 24 hours to obtain aldehyde-modified PVA.

[0022] Comparative Example 1 (the polycarboxylate water-reducing agent, the modifier, and the lignin fiber A are directly mixed to obtain the additive, and the remaining steps are the same as those in Example 1): S1: 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water are taken, and stirred evenly to obtain component A; 40 parts of hydroxyethyl acrylate, 60 parts of acrylic acid, 30 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water are taken, and stirred evenly to obtain component B; 250 parts of isopentanol polyoxyethylene ether and 50 parts of water are taken, and stirred evenly, and component A and component B are added dropwise at 50° C., and the addition time is 4 hours and 3.5 hours respectively. After the addition is completed, stir at room temperature for 4 hours, and adjust the pH to 7 to obtain a polycarboxylate water-reducing agent; S2: 25 parts of citric acid, 12 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 12 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 2 parts of (3-bromopropyl)trimethoxysilane, add to 60 parts of water and 20 parts of ethanol, heat to 45°C and stir for 2 hours, add 15 parts of 8mm lignin fiber, keep warm and stir for 4 hours, filter out the solid, dry, and obtain lignin fiber A; take 12 parts of polycarboxylate water reducer, 18 parts of lignin fiber A, and 6 parts of modifier, stir evenly, and obtain additive; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 80 parts of solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, spread half of it, compact it; spray the construction additive at a dosage of 0.12kg / m 2 , and the base layer is obtained; when the surface of the base layer is slurry-free and there is no water seepage, the other half of the solid waste composite stabilized material is spread for the second time, compacted, and the construction is completed after curing to obtain the comparative example 1 sample; The construction aid comprises: 8% sodium coconut oil hydroxyethyl sulfonate, 12% formaldehyde PVA, 5% PVA, 8% carboxyl-terminated silicone oil, and the balance is water; Preparation steps of aldehyde-modified PVA: Take 25 parts of 10% PVA aqueous solution, adjust the pH to 4, add 25 parts of 1 mol / L glutaraldehyde aqueous solution, and let stand at room temperature for 24 hours to obtain aldehyde-modified PVA.

[0023] Comparative Example 2 (the amount of solid waste mixture added was changed, and the other method steps were consistent with Example 1): S1: Take 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water, and stir evenly to obtain component A; take 40 parts of hydroxyethyl acrylate, 60 parts of acrylic acid, 30 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water, and stir evenly to obtain component B; take 250 parts of isopentanol polyoxyethylene ether and 50 parts of water, stir evenly, and add component A and component B dropwise at 50° C. The addition time is 4 hours and 3.5 hours respectively. After the addition is completed, stir at room temperature for 4 hours, adjust the pH to 7, and obtain a polycarboxylic acid water reducer; S2: 25 parts of citric acid, 12 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 12 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 2 parts of (3-bromopropyl)trimethoxysilane, add to 60 parts of water and 20 parts of ethanol, heat to 45°C and stir for 2 hours, add 15 parts of 8mm lignin fiber, keep warm and stir for 4 hours, filter out the solid, dry, and obtain lignin fiber A; take 12 parts of polycarboxylic acid water reducer, 18 parts of lignin fiber A, 6 parts of modifier, 100 parts of tetrahydrofuran, stir evenly, react at 75°C for 7 hours, remove the solvent, and obtain modified lignin fiber; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 100 parts of the solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, spread half of it, compact it; spray the construction additive at a dosage of 0.12kg / m 2 , and the base layer is obtained; when the surface of the base layer is slurry-free and there is no water seepage, the other half of the solid waste composite stabilized material is spread for the second time, compacted, and the construction is completed after curing, and the comparative example 2 sample is obtained; The construction aid comprises: 8% sodium coconut oil hydroxyethyl sulfonate, 12% formaldehyde PVA, 5% PVA, 8% carboxyl-terminated silicone oil, and the balance is water; Preparation steps of aldehyde-modified PVA: Take 25 parts of 10% PVA aqueous solution, adjust the pH to 4, add 25 parts of 1 mol / L glutaraldehyde aqueous solution, and let stand at room temperature for 24 hours to obtain aldehyde-modified PVA.

[0024] Comparative Example 3 (changing the amount of raw materials added in the modified lignin fiber, and the other method steps are consistent with Example 1): S1: Take 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water, and stir evenly to obtain component A; take 40 parts of hydroxyethyl acrylate, 60 parts of acrylic acid, 30 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water, and stir evenly to obtain component B; take 250 parts of isopentanol polyoxyethylene ether and 50 parts of water, stir evenly, and add component A and component B dropwise at 50° C., and the addition time is 4 hours and 3.5 hours respectively. After the addition is completed, stir at room temperature for 4 hours, adjust the pH to 7, and obtain a polycarboxylic acid water reducer; S2: 25 parts of citric acid, 12 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 12 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 2 parts of (3-bromopropyl)trimethoxysilane, add to 60 parts of water and 20 parts of ethanol, heat to 45°C and stir for 2 hours, add 15 parts of 8mm lignin fiber, keep warm and stir for 4 hours, filter out the solid, dry, and obtain lignin fiber A; take 8 parts of polycarboxylic acid water reducer, 18 parts of lignin fiber A, 10 parts of modifier, 100 parts of tetrahydrofuran, stir evenly, react at 75°C for 7 hours, remove the solvent, and obtain modified lignin fiber; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 80 parts of solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, spread half of it, compact it; spray the construction additive at a dosage of 0.12kg / m 2 , and the base layer is obtained; when the surface of the base layer is slurry-free and there is no water seepage, the other half of the solid waste composite stabilized material is spread for the second time, compacted, and the construction is completed after curing, and the comparative example 3 sample is obtained; The construction aid comprises: 8% sodium coconut oil hydroxyethyl sulfonate, 12% formaldehyde PVA, 5% PVA, 8% carboxyl-terminated silicone oil, and the balance is water; Preparation steps of aldehyde-modified PVA: Take 25 parts of 10% PVA aqueous solution, adjust the pH to 4, add 25 parts of 1 mol / L glutaraldehyde aqueous solution, and let stand at room temperature for 24 hours to obtain aldehyde-modified PVA.

[0025] Comparative Example 4 (the construction method was changed, and the remaining steps were the same as those in Example 1): S1: 1 part of ascorbic acid, 1 part of dodecyl mercaptan, and 15 parts of water were taken, and stirred evenly to obtain component A; 40 parts of hydroxyethyl acrylate, 60 parts of acrylic acid, 30 parts of maleic anhydride, 1 part of hydrogen peroxide, and 50 parts of water were taken, and stirred evenly to obtain component B; 250 parts of isopentanol polyoxyethylene ether and 50 parts of water were taken, and stirred evenly, and component A and component B were added dropwise at 50° C. The addition time was 4 hours and 3.5 hours respectively. After the addition was completed, the mixture was stirred at room temperature for 4 hours, and the pH was adjusted to 7 to obtain a polycarboxylic acid water reducer; S2: 25 parts of citric acid, 12 parts of ethyl bromide, 12 parts of sodium carbonate and 200 parts of tetrahydrofuran were stirred evenly, and reacted at 75°C for 6 hours to obtain modified citric acid; 12 parts of guar gum hydroxypropyltrimethylammonium chloride and 1 part of zinc sulfate were added, stirred evenly, stirred at 115°C for 10 hours, and the solvent was removed to obtain a modifier; S3: Take 2 parts of (3-bromopropyl)trimethoxysilane, add to 60 parts of water and 20 parts of ethanol, heat to 45°C and stir for 2 hours, add 15 parts of 8mm lignin fiber, keep warm and stir for 4 hours, filter out the solid, dry, and obtain lignin fiber A; take 12 parts of polycarboxylic acid water reducer, 18 parts of lignin fiber A, 6 parts of modifier, 100 parts of tetrahydrofuran, stir evenly, react at 75°C for 7 hours, remove the solvent, and obtain modified lignin fiber; S4: Take slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a ratio of 4:2:1:1:3 to obtain a solid waste composite material; take 400 parts of graded crushed stone, 25 parts of water, 28 parts of modified lignin fiber, and 80 parts of solid waste composite material, mix them evenly, and obtain a solid waste composite stabilized material; S5: Take the solid waste composite stabilized material, take the solid waste composite stabilized material, spread half of it, compact it, and get the base layer; when the surface of the base layer is slurry-free and there is no water seepage, spread the other half of the solid waste composite stabilized material for the second time, compact it, and complete the construction after curing to obtain the sample of comparative example 4.

[0026] In the above examples, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); ascorbic acid (CAS: 50-81-7); dodecyl mercaptan (CAS: 112-55-0); hydroxyethyl acrylate (CAS: 818-61-1); acrylic acid (CAS: 79-10-7); maleic anhydride (CAS: 108-31-6); hydrogen peroxide (35%, Nanjing Reagent); isopentanol polyoxyethylene ether (TPEG-2400, Nanjing Bermuda Biotechnology Co., Ltd.); citric acid (CAS :77-92-9); ethyl bromide (CAS: 74-96-4); sodium carbonate (CAS: 497-19-8); tetrahydrofuran (CAS: 109-99-9); guar hydroxypropyltrimethylammonium chloride (S26747, Shanghai Yuanye); zinc sulfate (CAS: 7733-02-0); (3-bromopropyl)trimethoxysilane (CAS: 51826-90-5); sodium cocoyl hydroxyethyl sulfonate (CAS: 61789-32-0); PVA (S30196, Shanghai Yuanye); glutaraldehyde (CAS: 111-30-8); carboxyl-terminated silicone oil (JS7889, Hubei Jusheng Technology Co., Ltd.).

[0027] Experiment: Take the 100mm×100mm×50mm samples prepared according to the method steps of Examples 1 to 3 and Comparative Examples 1 to 4, and refer to the "Highway Pavement Base Construction Technology Details JTGT F20-2015" to conduct mechanical property tests; the results are as follows: Compressive strength / MPa Splitting strength / MPa Example 1 8.9 6.9 Example 2 8.8 6.8 Example 3 8.8 6.9 Comparative Example 1 7.4 6.0 Comparative Example 2 8.1 6.3 Comparative Example 3 7.9 6.3 Comparative Example 4 7.7 6.1 Conclusion: It can be seen from the above table that in Comparative Example 1, the polycarboxylic acid water-reducing agent, the modifier, and the lignin fiber A are directly mixed to obtain the additive, and the performance is reduced; in Comparative Example 2, the amount of solid waste composite material added is changed, and the performance is reduced due to the adverse effect of its stability; in Comparative Example 3, the amount of raw materials added in the modified lignin fiber is changed, the amount of polycarboxylic acid water-reducing agent added is reduced, and the amount of modifier added is increased. Due to the change in properties such as fluidity, the performance is reduced; in Comparative Example 4, the construction method is changed, and the construction additive is not used. The performance is significantly reduced, which shows the importance of the construction method of the present invention; In summary, a solid waste composite stabilizing material provided by the present invention has good mechanical properties, and the mechanical properties can be further improved by adopting the construction process of the present invention.

[0028] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A solid waste composite stabilization material, characterized by: The invention comprises the following raw materials, calculated by weight: 400-450 parts of graded crushed stone, 20-25 parts of water, 25-30 parts of modified lignin fiber, and 70-80 parts of solid waste composite material; the solid waste composite material comprises slag powder, composite alkali slag powder, fly ash, steel slag powder, and desulfurized gypsum in a weight ratio of (4-5): (2-3): 1:1: (2-3).

2. The solid waste composite stabilized material according to claim 1, characterized in that: The preparation of the modified lignin fiber comprises the following steps: step 1: taking ascorbic acid, dodecyl mercaptan and water, stirring evenly to obtain component A; taking hydroxyethyl acrylate, acrylic acid, maleic anhydride, hydrogen peroxide and water, stirring evenly to obtain component B; taking isopentanol polyoxyethylene ether and water, stirring evenly, adding component A and component B dropwise at 40-50° C., the adding time is 3-4 hours and 3-3.5 hours respectively, stirring at room temperature for 2-4 hours after the adding is completed, adjusting the pH to 6-7, and obtaining a polycarboxylic acid water reducer; Step 2: Add citric acid, ethyl bromide and sodium carbonate into tetrahydrofuran, stir evenly, and react at 70-80°C for 5-7h to obtain modified citric acid; add guar gum hydroxypropyltrimethylammonium chloride and zinc sulfate, stir evenly, stir at 110-120°C for 8-10h, remove the solvent, and obtain a modifier; Step 3: Take (3-bromopropyl)trimethoxysilane, add it to water and ethanol, heat to 40~50℃ and stir for 1~2h, add lignin fiber, keep warm and stir for 4~6h, filter out the solid, dry it, and obtain lignin fiber A; take polycarboxylic acid water reducer, lignin fiber A, modifier, tetrahydrofuran, stir evenly, react at 70~80℃ for 6~7h, remove the solvent, and obtain modified lignin fiber.

3. A solid waste composite stabilized material according to claim 2, characterized in that: The polycarboxylate water-reducing agent comprises the following raw materials, calculated by weight: 1-2 parts of ascorbic acid, 1-2 parts of dodecyl mercaptan, 40-50 parts of hydroxyethyl acrylate, 50-60 parts of acrylic acid, 30-40 parts of maleic anhydride, 1-2 parts of hydrogen peroxide, and 250-260 parts of isopentanol polyoxyethylene ether.

4. The solid waste composite stabilized material according to claim 2, characterized in that: The modifier comprises the following raw materials, calculated by weight: 20-25 parts of citric acid, 8-12 parts of ethyl bromide, 10-12 parts of sodium carbonate, 180-220 parts of tetrahydrofuran, 8-12 parts of guar gum hydroxypropyltrimethylammonium chloride, and 0.5-1 part of zinc sulfate.

5. The solid waste composite stabilized material according to claim 2, characterized in that: The lignin fiber A comprises the following raw materials, calculated by weight: 1-2 parts of (3-bromopropyl)trimethoxysilane and 10-15 parts of lignin fiber; The modified lignin fiber comprises the following raw materials, calculated by weight: 10-15 parts of polycarboxylate water reducer, 15-20 parts of lignin fiber A, and 5-8 parts of modifier.

6. The solid waste composite stabilized material according to claim 5, characterized in that: The length of the lignin fiber is 6-10 mm.

7. The solid waste composite stabilized material according to claim 1, characterized in that: The graded crushed stone comprises the following raw materials, in terms of mass percentage: 25-30% of 50-150 mm limestone, 20-25% of 20-50 mm limestone, 15-20% of 10-20 mm limestone, and the remainder of 5-10 mm limestone.

8. A construction process for a solid waste composite stabilized material according to any one of claims 1 to 7, characterized in that: The following steps are involved: Take the solid waste composite stabilized material, spread it, and compact it; spray the construction aid to obtain a base layer; when the surface of the base layer is slurry-free and there is no water seepage, spread the solid waste composite stabilized material for the second time, compact it, and complete the construction after curing; the construction aid includes the following raw materials, by mass percentage: 6-8% sodium coconut oil hydroxyethyl sulfonate, 8-12% formaldehyde PVA, 5-6% PVA, 5-10% carboxyl-terminated silicone oil, and the balance is water.

9. The construction process of a solid waste composite stabilized material according to claim 8, characterized in that: The spraying amount of the construction additive is 0.1~0.15kg / m 2 .

10. The construction process of a solid waste composite stabilized material according to claim 8, characterized in that: Preparation of the aldehyde-modified PVA The method comprises the following steps: taking 20 to 30 parts of a 10 wt% PVA aqueous solution, adjusting the pH value to 3 to 4, adding 20 to 25 parts of a 1 mol / L glutaraldehyde aqueous solution, and standing at room temperature for 24 hours to obtain the aldehyde-modified PVA.

Citation Information

Patent Citations

  • Polycarboxylic acid slump retaining agent and preparation method thereof

    CN110358022A

  • BRT station heavy traffic road section pavement structure and construction method

    CN113863082A

  • High-performance low-carbon concrete

    CN115536347A

  • Inorganic binder stabilized gold tailing mixture and preparation and construction method thereof

    CN117819887A